2020
DOI: 10.1039/c9cp06808b
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the 2D-IR repertoire of the –SCN label to study site-resolved dynamics and solvation in the calcium sensor protein calmodulin

Abstract: 2D-IR spectroscopy of site-specifically incorporated –SCN labels in the calcium sensor protein calmodulin reveals local dynamics and solvation as they change upon calcium uptake and protein–ligand interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 63 publications
0
39
0
Order By: Relevance
“…In the present study, real-time measurement of Ca 2+ flux showed that Ca 2+ influxes in the Low OA group were the highest, followed by those of the control group, and Ca 2+ influxes in the High OA group were the lowest among these three groups. Greater Ca 2+ uptake in the control group and the Low OA group is associated with higher concentrations of intracellular Ca 2+ ; thus, more Ca 2+ interacts with calmodulin, which serves as the dynamic Ca 2+ protein sensor in eukaryotes ubiquitously and transmits calcium signals downstream 33 . Therefore, intracellular H 2 O 2 and Ca 2+ increased in the Low OA group but decreased in the High OA group compared to the control group.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, real-time measurement of Ca 2+ flux showed that Ca 2+ influxes in the Low OA group were the highest, followed by those of the control group, and Ca 2+ influxes in the High OA group were the lowest among these three groups. Greater Ca 2+ uptake in the control group and the Low OA group is associated with higher concentrations of intracellular Ca 2+ ; thus, more Ca 2+ interacts with calmodulin, which serves as the dynamic Ca 2+ protein sensor in eukaryotes ubiquitously and transmits calcium signals downstream 33 . Therefore, intracellular H 2 O 2 and Ca 2+ increased in the Low OA group but decreased in the High OA group compared to the control group.…”
Section: Discussionmentioning
confidence: 98%
“…Important properties of chemical systems, from water to polymers, are determined by their molecular level dynamics. , Ultrafast time-resolved IR spectroscopy is particularly well-suited for investigating the relationships among dynamics, interactions, and structures because it can measure properties such as orientational relaxation and spectral diffusion of a vibrational probe molecule. Such measurements can be used to investigate dynamics and how they are influenced by local and mesoscopic environments. ,,,, A successful experiment requires the detection of a spectrally resolved vibrational signal, ideally from a vibration with a lifetime at least as long as the dynamics of interest. , However, the native structures of many chemical systems suffer from overlapping signals and short vibrational lifetimes, , which are frequently not sufficient to fully capture the time range of the dynamic processes of interest.…”
Section: Introductionmentioning
confidence: 99%
“…These challenges have been circumvented by using vibrational probes. Vibrational probes are molecules that absorb infrared (IR) light, typically in the mid-IR region. , Their use became common practice in pump–probe and 2D IR spectroscopy, as it is possible to find probes with a spectrally resolved resonance that offers a sufficiently long vibrational lifetime. An additional desirable characteristic of vibrational probes is sensitivity to local environments, which makes it possible to investigate structural dynamics .…”
Section: Introductionmentioning
confidence: 99%
“…Simulation parameters are representative of a cyanylated cysteine residue in the calmodulin protein. 17 The second Kubo component is treated as static on the time scale of the waiting-time measurements by holding τ 2 constant at 1 ns. The transient absorption spectrum in panel (A) and the 2D IR spectrum in panel (B) at T W = 0 ps illustrates just how modest the quality of the raw data is at 10:1 SNR.…”
Section: Resultsmentioning
confidence: 99%